2007
DOI: 10.1007/s00432-007-0249-2
|View full text |Cite
|
Sign up to set email alerts
|

Expression of aromatase and estrogen sulfotransferase in preinvasive and invasive breast cancer

Abstract: We have demonstrated the presence of both aromatase and EST in malignant epithelium and adjacent stromal fibroblasts in DCIS. Lower stromal aromatase expression in preinvasive breast cancer and lower EST levels in high-grade DCIS suggest that the net effect of intratumoral estradiol (E2)-modulating enzymes results in lower local E2 levels in earlier stages of breast tumorigenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
16
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 22 publications
3
16
0
Order By: Relevance
“…In relation to the nuclear grade our results are similar to those found by Hudelist et al (2008) 12 ,who evaluated 96 samples of DCIS, and 104 samples of DCIS and IDC in the same samples. They found that in DCIS there was no statistically significant difference in aromatase expression between high, moderate and low grade tumors.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In relation to the nuclear grade our results are similar to those found by Hudelist et al (2008) 12 ,who evaluated 96 samples of DCIS, and 104 samples of DCIS and IDC in the same samples. They found that in DCIS there was no statistically significant difference in aromatase expression between high, moderate and low grade tumors.…”
Section: Discussionsupporting
confidence: 89%
“…It is found in women of reproductive age and also in post-menopausal 1,3 . The great difference between these two phases of life is that in postmenopausal women extra-ovarian aromatase plays a fundamental role in the estrogen synthesis (7,12) . The peripheral conversion of androgens to estrogens occurs in the adipose tissue, muscle, skin and also in the breast tissue itself and especially in the latter, significant enhancement of conversion due to higher levels of aromatase expression is associated with malignant changes 10,35,36 .…”
Section: Discussionmentioning
confidence: 99%
“…The results show that estrogen synthesis should be more expressive in tissues adjacent to the tumor, modulating tumor growth through paracrine, autocrine and intracrine mechanisms. 15,16 Though we found a trend towards greater aromatase expression in cases of nuclear grade III DCIS with comedonecrosis, the data were not statistically significant and similar to other findings described in the literature. 7 Greater aromatase expression has been been found in cases of nuclear grade III IDCs (p = 0.03), 4 similar to what we found in analyzing IDCs (p = 0.05).…”
Section: Discussionsupporting
confidence: 74%
“…While the presence of such enzymes in the primary tumor has been demonstrated previously, considerably less is known about such a network in corresponding lymph nodes [13]. This is somewhat surprising since tumor cells have been shown to lose estrogen responsiveness as they progress and develop distant metastases.…”
Section: Discussionmentioning
confidence: 91%
“…Suzuki et al [32] found a significant inverse correlation of EST with tumor size and lymph node status, and a positive correlation with a decreased risk of recurrence. Hudelist et al [13] investigated the differential expression of EST in preinvasive and invasive breast cancer and found a significant downregulation in high-grade DCIS compared to non-high-grade cases. To date, sulfotransferase expression in lymphatic metastases has never been investigated.…”
Section: Discussionmentioning
confidence: 98%